2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--33386
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Calculus I on Engineering Student Persistence

Abstract: I have a B.S. in civil engineering and a M.S. in structural engineering from Arizona State University. After graduating, I became a lecturer at ASU in civil engineering. During my time teaching I really became interested in engineering education and knew I wanted to pursue a graduate degree in that field. After moving to Utah and finding the program at Utah State University, I have really enjoyed diving in to the education world. I am most interested in the sophomore level courses that engineering students typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Of particular interest were two studies that compared persisting students to leaving students. Baisley and Adams [12] looked specifically at Calculus I and found that persisting students averaged a B grade in Calculus I, while non-persisters averaged a C+. Interestingly, of students with low grades who retook the class, 48% of them were successful and persisted in engineering.…”
Section: Math Performance As a Significant Predictor Of Retentionmentioning
confidence: 99%
“…Of particular interest were two studies that compared persisting students to leaving students. Baisley and Adams [12] looked specifically at Calculus I and found that persisting students averaged a B grade in Calculus I, while non-persisters averaged a C+. Interestingly, of students with low grades who retook the class, 48% of them were successful and persisted in engineering.…”
Section: Math Performance As a Significant Predictor Of Retentionmentioning
confidence: 99%
“…Across the country, engineering retention rates are often low (approximately 50%) and highly correlated with calculus performance [e.g., 1,2]. In fact, some authors assert that the biggest factor contributing to the attrition of first-year engineering students is inadequate mathematics performance [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some authors assert that the biggest factor contributing to the attrition of first-year engineering students is inadequate mathematics performance [3]. As such, early calculus courses are often considered to be barrier courses, due to several issues, including perceived rigor [3], poor math preparedness [4], lecture-based teaching methods [5], and lack of engineering context [1]. For students, poor calculus performance can contribute to low grade point averages, disqualification from scholarships, poor academic standing, and consequently a desire to leave engineering or college all together [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations